The adverse events and hemodynamic effects of adenosine-based cardiac MRI - Voigtländer, Thomas; Schmermund, Axel; Bramlage, Peter; Elsässer, Amelie; Magedanz, Annett; Kauczor, Hans-Ulrich; Mohrs, Oliver K. (Korean journal of radiology, 2011)
Voigtländer T, et al. Korean J Radiol. 2011 Jul-Aug;12(4):424-430. https://doi.org/10.3348/kjr.2011.12.4.424